Prevalence and Risk Factors of Scabies in Cats at Koiverde Petcare Clinic during 2022 - Kamil, Farid Ikram; Narindria, Yasmin Nadhiva; Notodiputro, Khairil Anwar; Indahwati, Indahwati; Mualifah, Laily Nissa; Putra, Stefanus Morgan Setyadi Perdana (Universitas Syiah Kuala, 2024)
Scabies is a skin disease caused by Sarcoptes scabiei or Notoedres cati mites in the corneum layer of the skin. This case study aimed to determine the prevalence and risk factors affecting the incidence of scabies in cats. Medical record data were obtained from Koiverde Petcare clinic from January to December 2022. The data obtained were then processed with binary logistic regression analysis and Odds Ratio (OR) using Minitab 19 for Windows software. OR value of the risk factors of breeds, sex and age were evaluated. Based on the results of the study, the prevalence rate of scabies in January-December 2022 period at the Koiverde Petcare clinic was 2.84%. The breeds most at risk of being infected with scabies was the Himalayan breed (X16), the sex most at risk of being infected was male (X21), and the age of the cat most at risk of being infected with scabies was the young age of the cat.